English grammar : an introduction - Collins, Peter, 1950-; Hollo, Carmella (New York : Palgrave Macmillan, 2017)
"This new edition of a successful text has been thoroughly revised to make it even more accessible to those without any prior grammatical knowledge. There is greater discussion and exemplification of key terms, while essential topics are now fully introduced at the outset. There are also new sections, more diagrams and shaded boxes"--Provided by publisher.
pt. A. Grammatical description. Introduction -- A preliminary overview -- Nouns and noun phrases -- Verbs and verb phrases -- Adjectives, adverbs, prepositions and associated phrases -- Clause structure and clause type -- Subordination and coordination -- Information structure in the clause -- pt. B. Looking at language in context. From separate sentences to connected texts -- Text and context -- Text analysis - putting it all together.
Includes bibliographical references (pp. 277-278) and index.
Keywords: English language -- Grammar